Method of edge-functionalizing 2D materials

By controlling the mixing of 2D materials at specific temperatures, adding oxidants and multifunctional group molecules to form edge functionalized 2D materials, the randomness of the functionalization process in the prior art is solved, efficient and environmentally friendly 2D material modification is achieved, and an orderly film is formed, and electrical and thermal conductivity is retained.

CN120418196AInactive Publication Date: 2025-08-01NATIONAL UNIVERSITY OF SINGAPORE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280101198.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2025-08-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the functionalization process of 2D materials is highly random, resulting in disorder affecting the original characteristics. Improved functionalization methods are needed to preserve the electronic and structural properties of 2D materials while modifying the macro properties.

Method used

Controllingly modifying the 2D material by mixing the 2D material with the solvent at a specific temperature, adding oxidizing agents and polyfunctional molecules, adjusting the temperature and adding quenching agents, forming a suspension to achieve edge functionalization of the 2D material.

Benefits of technology

Without damaging the base surface of the 2D material, it significantly improves its solubility and dispersion in water and polar solvents, forming a highly ordered film, retaining electrical and thermal conductivity, and is suitable for complex surfaces and confined spaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120418196A_ABST
    Figure CN120418196A_ABST
Patent Text Reader

Abstract

The present invention provides a method of forming an edge-functionalized 2D material, the method comprising mixing a 2D material with a solvent at a first predetermined temperature, adding an oxidant and a polyfunctional molecule, adjusting the temperature to a second predetermined temperature, adjusting the temperature to a third predetermined temperature, and adding a quencher to form a suspension, wherein the suspension comprises an edge-functionalized 2D material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to methods for functionalizing two-dimensional (2D) materials, particularly methods for forming edge-functionalized 2D materials. Background Art

[0002] One of the most important features of two-dimensional (2D) materials is that they are pure surface structures, that is, they have two surfaces but no three-dimensional (3D) bulk structure. Therefore, surface functionalization techniques can be used to change their physical and chemical properties, thus creating a large number of possibilities in terms of structure and function. For example, graphene, the most common 2D material, is hydrophobic in its pure form and can be functionalized by oxidation to produce graphene oxide (GO) and thus become hydrophilic. Therefore, surface functionalization of 2D materials has become a very effective method for customizing the properties of 2D materials. However, the functionalization process is inherently random. Exogenous atoms and exogenous molecules used for functionalization attach themselves to vacancies, sp 3 defects such as defects, and due to their low energy barrier for chemical reactions, a high degree of disorder is introduced. For example, graphene is an electrical conductor and a thermal conductor, while GO is a highly disordered electrical insulator and thermal insulator. Therefore, introducing disorder into the basal plane of 2D materials will affect many desirable properties of the original 2D materials.

[0003] Therefore, there is a need for improved methods for functionalizing 2D materials. Summary of the Invention

[0004] The present invention aims to solve these problems and / or provide improved methods for functionalizing 2D materials.

[0005] According to a first aspect, the present invention provides a method for forming an edge-functionalized 2D material, the method comprising:

[0006] - mixing the 2D material with a solvent at a first preset temperature to form a dispersion;

[0007] - adding an oxidizing agent and a polyfunctional molecule to the dispersion;

[0008] - adjusting the temperature to a second preset temperature and maintaining for a preset period of time;

[0009] - adjusting the temperature to a third preset temperature; and

[0010] - adding a quenching agent to form a suspension, wherein the suspension comprises an edge-functionalized 2D material.

[0011] The solvent can be any suitable solvent. For example, the solvent can be, but is not limited to, an oxidizing acid.

[0012] Mixing can be carried out under suitable conditions. For example, mixing can be carried out at a first preset temperature, which can be any suitable temperature. For example, the first preset temperature can be ≤ 10 °C.

[0013] Mixing can include mixing an appropriate amount of solvent with the 2D material. According to a particular aspect, mixing includes mixing the solvent with the 2D material at a weight ratio of 8:1 to 28:1.

[0014] Adding an oxidizing agent and a multi-functional group molecule can include adding any suitable oxidizing agent and multi-functional group molecule respectively. For example, the multi-functional group molecule can include, but is not limited to, multi-functional group alcohols, multi-functional group amines, amino alcohols, thiols, or mixtures thereof.

[0015] According to a specific aspect, adding an oxidizing agent and a multi-functional group molecule to the dispersion can include adding the oxidizing agent and the multi-functional group molecule sequentially. Specifically, the oxidizing agent can be first added to the dispersion, and then the multi-functional group molecule. Even more specifically, the multi-functional group molecule can be added to the dispersion after a period of time after adding the oxidizing agent. For example, the above period of time can be any suitable period of time. According to a particular aspect, the period of time can be 1 minute to 15 minutes.

[0016] Adjusting the temperature to a second preset temperature can include adjusting the temperature to any suitable temperature. For example, the second preset temperature can be ≤ 25 °C.

[0017] Adjusting the temperature to a second preset temperature can include maintaining the temperature at the second preset temperature for any suitable period of time. For example, the preset period of time can be ≤ 60 minutes.

[0018] Adjusting the temperature to a third preset temperature can include adjusting the temperature to any suitable temperature. For example, the third preset temperature can be ≤ 10 °C.

[0019] Adding a quenching agent can include adding any suitable quenching agent. For example, the quenching agent can be, but is not limited to, a reducing agent for quenching oxidation and quenching functionalization of the 2D material.

[0020] The method can further include separating the precipitate from the suspension formed after adding the quenching agent, wherein the precipitate contains edge-functionalized 2D material. The separation can be carried out by any suitable method.

[0021] According to a further aspect, the formed edge-functionalized 2D material can form a thin film. Description of the Drawings

[0022] In order that the present invention can be fully understood and easily put into practice, it will now be described by way of non-limiting examples, only as exemplary embodiments, and this description should refer to the accompanying illustrative drawings. In the drawings:

[0023] Figure 1 Schematic diagram showing the setup of a method according to an embodiment of the present invention;

[0024] Figure 2 Raman spectra showing different intensity distributions on the basal plane and edges of an edge-functionalized graphene material;

[0025] Figure 3 UV-Vis spectrum of the edge-functionalized graphene material is shown;

[0026] Figure 4 Raman spectrum is shown, which shows the average intensity and normalized intensity of the D-band, G-band and 2D-band of the edge-functionalized graphene material, with the results of graphene as a reference;

[0027] Figure 5 Schematic diagram showing the setup of a method according to an embodiment of the present invention; and

[0028] Figure 6 Schematic diagram of a method for obtaining a highly ordered thin film using an edge-functionalized 2D material formed according to an embodiment of the present invention. Detailed Description of the Invention

[0029] As described above, a method for functionalizing 2D materials that needs improvement is required.

[0030] Generally, the present invention relates to an improved and controlled method for functionalizing 2D materials with minimal impact on the 2D basal plane. The edges of 2D materials are one-dimensional (1D) structures. By functionalizing the 1D edges, the electronic and structural properties of the basal plane can be retained while the macroscopic properties of the 2D material can be modified. In addition, the method is based on a 2D material modified in a mild and selective manner, making the method reproducible and environmentally friendly compared to prior art methods.

[0031] According to a first aspect, the present invention provides a method for forming an edge-functionalized 2D material, the method comprising:

[0032] - Mixing a 2D material with a solvent at a first preset temperature to form a dispersion;

[0033] - Adding an oxidizing agent and a multi-functional group molecule to the dispersion;

[0034] - Adjusting the temperature to a second preset temperature and maintaining for a preset time;

[0035] - Adjusting the temperature to a third preset temperature; and

[0036] - Adding a quenching agent to form a suspension, wherein the suspension comprises an edge-functionalized 2D material.

[0037] The 2D material can be any suitable 2D material. For example, the 2D material can be, but is not limited to, graphene, graphyne, graphane, borophene, boron nitride, germanene, silicene, stanine, plumbene, antimonene, bismuth hydride, phosphorene, transition metal dichalcogenides, such as two-dimensional transition metal carbides, nitrides, and carbonitrides (MXene) including transition metal carbides, transition metal nitrides, and transition metal carbonitrides, or combinations thereof. According to a particular aspect, the 2D material can be graphene, boron nitride, or a combination thereof.

[0038] The solvent can be any suitable solvent. The solvent can be an acid, preferably an inorganic acid. According to a particular aspect, the solvent can be, but is not limited to, an oxidizing acid. For example, the solvent can be, but is not limited to: sulfuric acid, nitric acid, phosphoric acid, perchloric acid, iodic acid, chromic acid, or mixtures thereof.

[0039] During the mixing process, an appropriate amount of the solvent and the 2D material can be mixed. According to a particular aspect, the mixing can include mixing the solvent and the 2D material at a weight ratio of 8:1 to 28:1. For example, the weight ratio of the solvent to the 2D material can be 10:1 to 25:1, 12:1 to 20:1, 13:1 to 19:1, 15:1 to 18:1, 16:1 to 17:1. Even more specifically, the weight ratio of the solvent to the 2D material can be 12:1 to 14:1.

[0040] The mixing can be carried out under suitable conditions. For example, the mixing can be carried out at a first preset temperature, which can be any suitable temperature. According to a particular aspect, the first preset temperature can be ≤10°C. In particular, the first preset temperature can be 1°C to 10°C, 2°C to 9°C, 3°C to 8°C, 4°C to 7°C, 5°C to 6°C. Even more specifically, the first preset temperature can be 1°C to 10°C.

[0041] Adding the oxidant and the multifunctional molecule can include adding any suitable oxidant and multifunctional molecule, respectively. For example, the multifunctional molecule can include any suitable multifunctional molecule based on the desired functionalization of the 2D material. According to certain aspects, the multifunctional molecule can be a multifunctional molecule comprising terminal functional groups based on oxygen, nitrogen, sulfur, phosphorus, boron and / or silicon. In particular, the multifunctional molecule can be, but is not limited to, a multifunctional alcohol, a multifunctional amine, an amino alcohol, a thiol, or a mixture thereof. For example, when the multifunctional molecule is water, functional groups such as -OH- and -O- can be generated, while when the multifunctional molecule is a diamine or a diol, the functional groups can be -RNH2- or -ROH, respectively. Other examples include, but are not limited to, glycols, ethylene glycol, triethylene glycol, glycerol, erytrytol, diamines, ethylenediamine, diethylenetriamine, triethylenetetamine, triethyleneglycol diamine, diaminodiphenylmethane, melamine, leucinol, valinol, alaninol, cysteine, thioalanine, or mixtures thereof.

[0042] Adding the oxidant and the multifunctional molecule to the dispersion may comprise adding the oxidant and the multifunctional molecule simultaneously or sequentially. According to certain aspects, adding the oxidant and the multifunctional molecule to the dispersion may comprise adding the oxidant and the multifunctional molecule sequentially. Specifically, the oxidant may be added to the dispersion first, followed by the multifunctional molecule. The multifunctional molecule may be added to the dispersion some time after the addition of the oxidant. The some time may be any suitable some time. For example, the some time may be after the oxidant may have dissolved into the dispersion to form a homogeneous solution. According to certain aspects, the some time may be ≤15 minutes. For example, the some time may be from 1 minute to 15 minutes. Specifically, the some time may be from 1 minute to 12 minutes, from 2 minutes to 10 minutes, from 3 minutes to 9 minutes, from 4 minutes to 8 minutes, or from 5 minutes to 7 minutes.

[0043] According to a particular aspect, during the addition of the oxidant and the multifunctional molecule, the temperature of the dispersion can be maintained at a first preset temperature. Specifically, the temperature of the dispersion can be maintained at a temperature of ≤10°C. Specifically, the temperature can be maintained at a temperature of 1°C to 10°C, 2°C to 9°C, 3°C to 8°C, 4°C to 7°C, 5°C to 6°C. Even more specifically, the temperature can be maintained at 5°C to 10°C. With the addition of the oxidant, free radicals can begin to form. However, when the temperature during the formation of free radicals is maintained at a lower level, the reactivity of the free radicals is also reduced, and the embedding is reduced. At the same time, the reactivity at the edge of the 2D material is increased compared to the reactivity at the base surface, which greatly facilitates the functionalization of the edge of the 2D material.

[0044] After adding an oxidizing agent and a multi-functional molecule, the temperature can be adjusted to a second preset temperature. Adjusting the temperature to the second preset temperature can include adjusting the temperature to any suitable temperature. For example, the second preset temperature can be the same as the first preset temperature, or the second preset temperature can be ≤25 °C. Specifically, the second preset temperature can be 1 °C to 25 °C, 10 °C to 23 °C, 12 °C to 22 °C, 15 °C to 20 °C, 17 °C to 18 °C. Even more specifically, the second preset temperature can be 10 °C to 25 °C.

[0045] The adjustment can include adjusting the temperature to the second preset temperature by any suitable means. For example, the adjustment can include not providing any cooling so as to allow the temperature to rise naturally. Alternatively, an external heating device can be provided. Regardless of the heating method, the heating rate can be any suitable heating rate. For example, the heating rate can be a heating rate of 2 °C / minute to 4 °C / minute.

[0046] Adjusting the temperature to the second preset temperature can include keeping the temperature constant, or maintaining the second preset temperature for any suitable period of time. For example, the preset period of time can be ≤60 minutes. Specifically, the preset period of time can be 5 minutes to 60 minutes, 7 minutes to 58 minutes, 10 minutes to 55 minutes, 15 minutes to 50 minutes, 20 minutes to 45 minutes, 25 minutes to 40 minutes, 30 minutes to 35 minutes. Even more specifically, the preset period of time can be 20 minutes to 60 minutes.

[0047] Adjusting the temperature to a third preset temperature can include adjusting the temperature to any suitable temperature. According to a particular aspect, adjusting the temperature to the third preset temperature can include adjusting the temperature to a temperature lower than the second preset temperature. Specifically, the third preset temperature can be ≤10 °C. Specifically, the third preset temperature can be 1 °C to 10 °C, 2 °C to 9 °C, 3 °C to 8 °C, 4 °C to 7 °C, 5 °C to 6 °C. Even more specifically, the third preset temperature can be 5 °C to 10 °C.

[0048] The oxidation and functionalization of the 2D material can be stopped by adding a quenching agent. Thus, adding a quenching agent can include adding any suitable quenching agent. For example, the quenching agent can be, but is not limited to, a reducing agent for quenching the oxidation and quenching the functionalization of the 2D material. In particular, the quenching agent can be an inorganic reducing agent. For example, the quenching agent can be, but is not limited to, hydrogen peroxide, sodium thiosulfate, hydroxylamine hydrochloride, and sodium sulfite, or a mixture thereof.

[0049] Adding a quenching agent may include adding any suitable amount of the quenching agent. For example, the amount of the quenching agent added may depend on the amount of the oxidizing agent added when adding the oxidizing agent and the multi-functional molecule to the dispersion. In particular, the weight ratio of the oxidizing agent to the quenching agent may be 1:2, 1:1.8, 1:1.6, 1:1.5. For example, the weight ratio may be 1:1.6.

[0050] The method may further include separating a precipitate from the suspension formed after adding the quenching agent, wherein the precipitate comprises an edge-functionalized 2D material. The separation can be carried out by any suitable method. For example, the separation can be transferring the suspension through a separating funnel to separate the precipitated slurry from the suspension.

[0051] The method may further include cleaning and / or washing the precipitate. The cleaning and / or washing can use any suitable solvent. For example, the cleaning and / or washing can use but is not limited to water, HCl, ethanol or a mixture thereof.

[0052] According to other aspects, the formed edge-functionalized 2D material can form a thin film. The thin film can be formed at room temperature by a simple method and may not require any other post-treatment, such as thermal or chemical modification. Since the edge-functionalized 2D material can be partially intrinsically organized, obtaining organized thin films and bulk materials may require less total energy. In particular, the solvent dispersion of the edge-functionalized 2D material can be filtered or cast to form a highly organized thin film with high anisotropic conductivity and sufficient mechanical strength to form a free-standing thin film.

[0053] The thin film can be a free-standing thin film having characteristics such as a smooth surface and low surface roughness. In particular, the thin film can have a surface roughness of ≤1 μm. For example, the surface roughness can be about 5 nm to 950 nm, 10 nm to 900 nm, 20 nm to 800 nm, 30 nm to 700 nm, 50 nm to 600 nm, 75 nm to 500 nm, 100 nm to 400 nm, 200 nm to 300 nm. The thin film may comprise a well-oriented in-plane thin film having a dense cross-sectional profile. In particular, the cross-section of the formed thin film can have a thickness of ≤5 mm. Specifically, the thickness can be 3 μm to 400 μm, 5 μm to 250 μm, 10 μm to 200 μm, 50 μm to 150 μm, 75 μm to 100 μm.

[0054] The above method is a simple method for the selective functionalization of 2D materials. In particular, the method is a mild but selective method for modifying 2D materials, in which the degree of 1D edge functionalization is much higher compared to the 2D basal plane. Even more particularly, since the 2D basal plane is conserved, most of the original conductive properties of the 2D material can remain unchanged even after being edge-functionalized. Since the conductive properties are anisotropic, the creation of thin films with high electrical conductivity and high thermal conductivity in-plane rather than out-of-plane can be achieved.

[0055] In addition, the above method is a relatively fast method, in which the selective functionalization reaction can be achieved in less than or equal to about 2 hours.

[0056] Another advantage of the method is that the functionalized 2D materials are stable in water and other polar solvents and mixtures of solvents without losing their functionalized properties. In this way, the functionalized 2D materials can be stored as highly viscous liquids or highly concentrated pastes, which can be easily dispersed in water and other solvents without the need for harsh methods such as sonication.

[0057] Compared with traditional functionalization processes that use excessive amounts of strong acids and oxidants, which result in large amounts of chemical waste, the above method is more environmentally friendly and sustainable due to the much smaller amount of materials required. In addition, the edge functionalization method is based on 2D materials modified in a mild and selective manner, through an extreme adaptation of standard chemical oxidation methods, taking advantage of the higher reactivity and regioselective reactivity of 2D materials (1D edges relative to the 2D basal plane).

[0058] For example, both graphene and graphene oxide (GO) can be obtained from the same raw material (graphite), but they follow different processing routes. One 2D material is an excellent thermal and electrical conductor (graphene), while the other is an insulator (GO). Therefore, forming graphene films would be the logical path to obtain conductive films, but directly forming films from graphene is challenging due to its low solubility and strong aggregation tendency. The most common way to address these issues is to first prepare GO and then further chemically reduce it to produce reduced graphene oxide (rGO). The disadvantages of following this process route are:

[0059] - A long and expensive process that generates large amounts of chemical residues;

[0060] - Compared with graphene, rGO has significant defects and requires harsh annealing and graphitization processes (high temperatures) to partially repair the structural defects;

[0061] - The final desired product (e.g., GO film) must be reduced, annealed, and graphitized, and all these transformations inevitably press pores (e.g., from gas release) on the material, thereby reducing the density of the material and its overall electrical and thermal conductivities; and

[0062] - The high temperatures required for annealing and graphitization are typically above 1000 °C, which greatly limits their applications because few substrate materials of the target materials can withstand these post-treatment temperatures.

[0063] Therefore, in the above method, well-controlled modification can improve the processability of 2D materials without significantly damaging the 2D material sheets, thus not affecting their original properties. In addition, since functionalization generates a higher concentration of functional groups at the edges of 2D materials, the ordered interactions between the sheets are increased, thereby increasing the film-forming properties. Therefore, this method avoids harsh post-treatment and greatly increases the application scope of 2D films and other architectures.

[0064] In addition, higher reaction yields can be achieved. For example, values up to 30 g of product can be produced per liter of reactor (i.e., 3 kg of product can be produced per batch in a 100-liter reactor with a batch cycle as short as 2 hours). In addition, due to the accelerated nature of this method, they can be easily adapted to flow reactors without major process modifications, thereby further improving the reaction yield as a function of time. After the functionalization reaction, very different products can be obtained, such as but not limited to water-stable dispersions, highly concentrated and redispersible slurries, extruded or compressed films, ingots and filaments, unsupported films, and films deposited on complex textured surfaces.

[0065] In summary, the present invention provides a method for functionalizing 2D materials, which significantly improves their solubility / dispersibility in water and other polar solvents without losing most of the original properties of the 2D basal plane. Therefore, such materials allow the preparation of highly ordered films and other bulk structures that retain most of the characteristics of 2D materials, including extremely high anisotropic characteristics, even on textured surfaces and in confined geometries. Such structures are relevant to a wide variety of applications, including but not limited to thermal management, smart electronic devices, e-textiles, flexible and wearable electronics, sensors, filter membranes, batteries, and supercapacitors.

[0066] The present invention has been generally described above and will be more readily understood by reference to the following embodiments, which are provided by way of illustration and are not intended to be limiting.

[0067] Examples

[0068] Example 1 - Graphene Functionalization Using Water as a Multifunctional Molecule

[0069] The method is carried out using defined steps and semi-automatic settings to ensure reproducibility and reduce human intervention. A schematic diagram of the setting is shown as Figure 1 shown below.

[0070] First, concentrated sulfuric acid (95% to 98%) is added to the reactor and cooled to 5°C with continuous stirring. In sequence, graphene (or micronized graphite) is added to the sulfuric acid, and the graphene / acid ratio defines the final level of oxidation / functionalization. The maximum concentration supported to produce the slightest oxidation (due to viscosity limitations) is 210 mg of graphene per 1 mL of sulfuric acid.

[0071] After stirring until complete dispersion to form a black viscous liquid (about 5 minutes to 10 minutes), a 5% aqueous KMnO4 solution is slowly added using a peristaltic pump while maintaining the temperature constant at 5°C to 10°C. Depending on the volume and flow rate used in the reaction, this process proceeds for up to 1 hour, with the total amount of KMnO4 set at 133 mg / mL of sulfuric acid. At this stage, ·OH and ·O· free radicals are formed, but due to the low temperature, the reactivity of the free radicals is low. After adding KMnO4, the temperature is raised to 22°C and maintained for 20 minutes (oxidation / functionalization stage), and then cooled to 5°C again. Water and a 32% H2O2 solution are added to quench the reaction and consume the excess KMnO4.

[0072] The simple fact of using graphene instead of graphite eliminates (or significantly reduces) the sulfate intercalation process, avoids the confinement of acids and oxidants within the interlayer channels of graphite, and reduces the availability of these reactants to modify (and damage) the basal plane. In addition, since the temperature is kept low during free radical formation, the reduced intercalation is related to the decreased reactivity of the free radicals, and the increased reactivity of the graphene edges (relative to the basal plane) greatly favors the functionalization of the graphene edges, as Figure 2 shown below. In particular, Figure 2 shows the reduced defects in the 2D basal plane.

[0073] After the reaction, the resulting suspension is kept at 5°C, diluted (2 mL of H2O per 1 mL of sulfuric acid), quenched with a 35% H2O2 solution (0.06 mL of H2O2 per 1 mL of 5% KMnO4), and left to stir for 2 hours. The resulting suspension is transferred to a separating funnel and left overnight for precipitation. Subsequently, the precipitated slurry is separated and washed twice with 10% HCl (7 mL of HCl per 1 mL of sulfuric acid) for cleaning.

[0074] The resulting materials are stable in water and other polar solvents, allowing for high concentrations such as dispersions with concentrations as high as 10 mg / mL in water and 20 mg / mL in a water / isopropanol mixture (showing no precipitation for at least 24 hours). However, their physicochemical fingerprints are more similar to graphene, showing a very high carbon content (up to 90% C, and about 95% being sp 2 carbon) and a low C / O ratio (about 10, but can be adjusted according to the desired properties), which can be seen by X-ray photoelectron spectroscopy (XPS) and elemental analysis. They also exhibit high thermal stability in thermogravimetric analysis (TGA), and as seen by X-ray diffraction analysis (XRD), there are no intercalation peaks of oxygen on the basal plane.

[0075] Most interestingly, they form stable dispersions in water, allowing for liquid-phase ultraviolet-visible spectroscopy (UV-Vis) characterization, and presenting an absorption band at λ 最大 = 269 nm, as Figure 3 shown, which is characteristic of graphene. Finally, compared to GO and graphene, they show distinct changes in the Raman spectral curves in different sheet regions, with defects only located at the edges, as Figure 4 shown.

[0076] Example 2 - Graphene Functionalization Using Heteroatom Molecules as Multifunctional Molecules

[0077] Similar to the process of Example 1, this example provides a method for graphene functionalization using heteroatom molecules instead of water as multifunctional molecules. A schematic diagram of this method is as Figure 5 shown.

[0078] First, concentrated sulfuric acid (95% to 98%) is added to the reactor and cooled to 5°C with continuous stirring. Graphene is added in a suitable proportion to obtain the desired level of functionalization (Step 1, Figure 5 ). After stirring until the graphene is completely dispersed, forming a black viscous liquid (about 5 minutes to 10 minutes), water is added to the reactor to slightly reduce the viscosity, and then it reacts with KMnO4 to form O3, further inducing free radical formation (Step 2, Figure 5 ). The amount of water and the amount of added functionalized molecules are fixed at a molar ratio of 3:1 (water: multifunctional molecule). Subsequently, ground solid KMnO4 is slowly added using the solid dosing unit of the reactor, keeping the temperature constant at 5°C to 10°C. Depending on the reaction volume, this process takes about 1 hour, and the total amount of KMnO4 is set to 133 mg / mL of sulfuric acid. At this stage, the functionalized molecules (with the desired functional groups) are slowly added in excess to the system (about 30 wt% relative to the added graphene) (Step 4, Figure 5), and the formation of free radicals occurs (e.g., ·OR, ·NR, and ·SR), but due to the low temperature, the reactivity of the free radicals remains low. Subsequently, the temperature is raised to 22 °C for 20 to 60 minutes (depending on the reactivity of the applied molecule) (Step 5, Figure 5 ), and then cooled to 5 °C again.

[0079] After the reaction is completed, the resulting suspension is maintained at 5 °C, diluted (2 mL of H2O per 1 mL of sulfuric acid), quenched with 35% H2O2 solution (0.06 mL of H2O2 per 1 mL of 5% KMnO4), and left to stir for 2 h. Subsequently, the resulting suspension is transferred to a separating funnel and left overnight for precipitation. The precipitated slurry is separated and washed twice with 10% HCl (7 mL of HCl per 1 mL of sulfuric acid) for cleaning. For applications requiring higher purity, the washed slurry is dialyzed (10 kDa molecular weight membrane) until the pH stabilizes.

[0080] In addition to adding a smaller amount of water to react with KMnO4 (to minimize the interference of water with the reaction mechanism) ( Figure 5 Step 2 in Figure 5 ), adding KMnO4 in the form of solid powder ( Figure 5 Step 3 in Figure 5 ), and replacing part of the water (

[0081] Step 4 in

[0082] with another molecule that can easily carry relatively stable free radicals ( Figure 6 Step 4 in

[0083] ), most of the reactant ratios are the same as those in the water-based method of Example 1, preferably bifunctional molecules. In addition, the maximum concentration achieved by this method is slightly lower than that of the water-based process in Example 1, which is also due to the viscosity limitation imposed by the reduced amount of water added and may directly depend on the viscosity contribution of the molecule used for functionalization. Example 3 - Preparation of highly ordered thin films

[0082] A schematic diagram of the method for obtaining highly ordered thin films is as shown in Figure 6 shown.

[0083] To demonstrate the processability and film-forming characteristics of the functionalized graphene obtained in Example 1 (hereinafter referred to as "G sfw "), G sfw was redispersed in a water:isopropanol mixture (1:1 volume ratio) and sonicated in an ultrasonic bath (300 W) for 30 minutes. The resulting dispersion was centrifuged at 3000 rpm for 15 minutes and then centrifuged again at 6000 rpm for 15 minutes to remove any aggregates that might interfere with film formation. The resulting supernatant was a very homogeneous black dispersion with a liquid crystal appearance. The organization of the dispersion seems to be strongly assisted by the interaction between the functionalized regions (especially the edges) of G sfw and the solvent used. Although Gsfw It is also stable in pure water, but the dispersion produced by the water:isopropanol mixture is more ordered and stable. In addition, by directly solvent casting on a polytetrafluoroethylene mold and using a polytetrafluoroethylene (PTFE) filtration membrane (with a pore size of 0.2 μm to 1 μm, depending on the lateral size of the starting graphene), vacuum filtration is carried out, and the supernatant is applied to film formation. During filtration and solvent casting, the removal of the solvent from the dispersion forces the G sfw interactions between functional groups, increasing the organization and allowing G sfw the highly ordered deposition of the sheets ( Figure 6 , steps 3 and 4).

[0084] The connection between controlled functionalization and an appropriate solvent mixture strengthens the already anisotropic nature of the 2D material-based dispersion, promoting self-assembly during the film formation process. The resulting films are highly ordered black / silver films with a very smooth surface (roughness in the nanometer range). The films have very good in-plane orientation, a dense cross-section, and produce strong free-standing films with a cross-section as thin as 4 μm. These very ordered and dense films are obtained by direct casting / filtration at room temperature without any additional treatments including pressure, heat, or chemical modification. Films can be formed from various G sfw concentrations, allowing the formation of ordered films with a concentration as high as 10 mg / mL. However, the samples with the highest concentration exhibit increased surface roughness due to the high initial viscosity. According to a specific embodiment, the concentration for forming films without sacrificing structural order and surface smoothness can be ≤4 mg G per mL of water / isopropanol mixture sfw . This further confirms the conclusion that the high structural order of the films is a direct result of the anisotropy of the material and the solvent interactions during the initial film-forming stage, indicating a lower initial entropy and thus a correspondingly lower energy required to form highly ordered films.

[0085] In addition, when the formed films are simultaneously subjected to thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), they exhibit a defined exothermic transition at 197 °C with an enthalpy of 111 J / g and a loss of 3 wt% at the same temperature. This enthalpy may be related to the condensation reaction between functional groups (mainly composed of carboxyl and hydroxyl groups), which can react between the sheets to form ether bridges, ester bridges, and anhydride bridges. The mass loss observed by TGA is directly related to the evaporation of the water produced by these reactions (Equations 1 to 3).

[0086] R-OH + R’-OH → R-O-R’ + H2O (1)

[0087] R-COOH + R’-OH → R-COO-R’ + H2O (2)

[0088] R-COOH + R’-COOH → R-OCOCO-R’ + H2O (3)

[0089] The above reaction allows for further structuring and partial cross-linking of thin film structures, enables the enhancement of the thin film at a temperature much milder than the graphitization process, and avoids temperature-related application limitations.

[0090] Example 4 - Preparation of Conductive Thin Films on Complex Surfaces and in Confined Spaces

[0091] Since the use of the synthesis platform does not require harsh post-treatment of the formed thin films or structures, it opens up a wide range of applications for coating complex-structured surfaces and can be used in many different industries, from electronics to photonics. In this case, G sfw was applied to the surface of Si (coated with SiO2), whose micro-column array has 50×50 columns (column diameter 100 μm and column height 100 μm) within a 100 mm 2 area.

[0092] When forming a film on the micro-column textured substrate, 250 μL of a G sfw dispersion with a concentration of 4 mg / mL in water / isopropanol (1:1 ratio) was cast on the substrate surface to form stable droplets. The droplets were placed in a fume hood with a constant airflow for evaporation (about 30 minutes) to generate a 1 mg thin film (about 10 μm thick). Without any other treatment (nor drying), the substrate was subjected to Raman spectroscopy, atomic force microscopy (AFM), and SEM.

[0093] A very uniform G sfw coating was obtained, which formed a very tight attachment with the columns, had no obvious interfacial gaps, and the surface of the thin film was very smooth (surface roughness = 10 nm to 15 nm). In addition, the thin film was uniformly formed over the entire substrate, and the entire surface was evenly covered with a high-quality graphite film.

[0094] To demonstrate the good adhesion of the formed thin film on the column array and to show that it can be further processed, the same G sfw coated array was used in a new SiO2 deposition layer to confine the G sfw film in a dielectric / conductive / dielectric layer conformation. SEM images show different cross-sections of the partially deposited array as a function of the different electron densities of its top layer. However, the different elemental compositions of the cross-section can only be clearly detected when performing SEM-EDX and forming complete and separate elemental maps of C, O, and Si. The elemental maps show that in one cross-section (G sfw / SiO2), the surface is rich in C, and in another cross-section (SiO2 / G sfwThe Si- and O-rich surface of ( ) / SiO2 demonstrated the effectiveness of linking the casting of the resulting thin film with the deposition method to form a complex layered structure.

[0095] The thermal and electrical properties of the thin film were also characterized. Thermal characterization was performed using a laser flash analysis (LFA) device, and the thermal diffusivity of thin films with thicknesses ranging from a few micrometers to a few millimeters was measured. This flash analysis method involves applying energy at the bottom and then detecting it at the top, and is most suitable for measuring thermal diffusivity values up to 2000 mm 2 / s, resulting in thermal conductivity values higher than 1000 W / mK. With the help of a carefully designed mask and a thermal simulation model, in-plane and out-of-plane values of individual thin films were obtained.

[0096] For electrical characterization, measurements were made using a 4-probe sheet resistance setup (for in-plane) and a self-fabricated heterostructure stacked device (for out-of-plane). The former method consists of 4 equally spaced probes (two outer probes for applying the measurement current and two inner probes for measuring the voltage drop), and is widely used to measure the sheet resistance of thin films with a thickness less than 40% of the probe spacing (1 mm). Finally, for out-of-plane measurements, a 4-probe device was designed. In this case, the device uses metal electrodes (Cr 5 nm / Au 60 nm) deposited on the bottom and top, sandwiching the thin film.

[0097] The resulting thin film, without any post-treatment, has an in-plane thermal conductivity between 10 W / mK and 120 W / mK. The out-of-plane thermal conductivity is between 0.05 W / mK and 0.2 W / mK. Therefore, the formed thin film has a very high anisotropy ratio (about 850), and only 2D materials synthesized and designed using expensive methods such as chemical vapor deposition (CVD) can reach this value.

[0098] In terms of conductivity, the sheet resistance of the thin film is as low as 30 mOhm / sq, and the in-plane conductivity reaches above 100 kS / m, producing competitive values compared to other non-processable carbon thin films obtained through high-temperature / high-pressure processes. However, very different from most other commercial carbon thin films, the thin film formed in this example has anisotropic electrical properties, with its in-plane conductivity even lower than 1 S / m, resulting in an anisotropy ratio as high as ρ = 100000. Therefore, the formed thin film can be an in-plane conductor and an out-of-plane insulator.

[0099] Although the foregoing description describes exemplary embodiments, those skilled in the relevant art will understand that many variations can be made without departing from the present invention.

Claims

1. A method for forming an edge-functionalized 2D material, the method comprising: - Mixing a 2D material with a solvent at a first preset temperature to form a dispersion; - Adding an oxidant and a multi-functional molecule to the dispersion; - Adjusting the temperature to a second preset temperature and maintaining for a preset period of time; - Adjusting the temperature to a third preset temperature; and - Adding a quenching agent to form a suspension, wherein the suspension contains the edge-functionalized 2D material.

2. The method according to claim 1, wherein the solvent is an oxidizing acid.

3. The method according to claim 1 or 2, wherein the first preset temperature ≤ 10 °C.

4. The method according to any one of the preceding claims, wherein the mixing comprises mixing the solvent and the 2D material at a weight ratio of 8:1 to 28:

1.

5. The method according to any one of the preceding claims, wherein adding an oxidant and a multi-functional molecule to the dispersion comprises adding the oxidant and the multi-functional molecule sequentially.

6. The method according to claim 5, wherein adding an oxidant and a multi-functional molecule to the dispersion comprises adding an oxidant to the dispersion and then adding the multi-functional molecule after a period of time.

7. The method according to claim 6, wherein the period of time is 1 minute to 15 minutes.

8. The method according to any one of the preceding claims, wherein the multi-functional molecule comprises a multi-functional alcohol, a multi-functional amine, an amino alcohol, a thiol, or a mixture thereof.

9. The method according to any one of the preceding claims, wherein the second preset temperature ≤ 25 °C.

10. The method according to any one of the preceding claims, wherein the preset period of time ≤ 60 minutes.

11. The method according to any one of the preceding claims, wherein the third preset temperature ≤ 10 °C.

12. The method according to any one of the preceding claims, wherein the quenching agent is a reducing agent for quenching the oxidation and functionalization of the 2D material.

13. The method according to any one of the preceding claims, wherein the method further comprises separating a precipitate from the suspension formed after adding the quenching agent, wherein the precipitate contains the edge-functionalized 2D material.

14. The method according to any one of the preceding claims, wherein the formed edge-functionalized 2D material further forms a thin film.